Development of Internationalization Program Guide for Early Childhood Teacher Education Department - Wantoro Wantoro; Diana Diana; Yuli Kurniawati Sugiyo Pranoto (Universitas Negeri Semarang, 2024)
The research aims to explore practical experiences related to the implementation of internationalization in PGPAUD study programs/departments that already have international classes. The approach used is descriptive quantitative research, with the research sample being lecturers and students in the international class, a total of 15 lecturers and 15 students, each taken from 5 classes in three batches. The results showed that the implementation of the learning process in the international class was generally the same for learning activities, starting with prayer, delivery of apperceptions and materials, group discussions in the form of case studies or project approaches. In addition, at the beginning of the first meeting, lecturers usually provide reinforcement and motivation for students in international classes. The facilities and infrastructure provided in the international class are adequate, starting from classrooms, internet networks and lecture materials. The need for program guidelines will guide students in carrying out lectures while in international classes.